Towards Virtual Mobility Support in a Federated Testbed for Wireless Sensor Networks - Braun, Torsten; Coluson, Geoff; Staub, Thomas (Electronic Communications of the EASST, 2011)
We present a design that accommodates ‘virtual mobility’ in a wireless sensor network testbed. Virtually-mobile nodes can be physical, simulated or emulated, and virtual mobility for all three types is treated uniformly by embedding the nodes in a virtual space. In operation, the traffic of virtually-mobile nodes is intercepted and redirected to a mobility model from where it is selectively forwarded to other nodes that are virtually in range. We present a distributed implementation architecture that potentially allows the simulation/emulation of large-scale wireless sensor networks with large numbers of virtually-mobile nodes.